A Legal Inquiry into the Proliferation and Control of Small Arms in Nigeria - Okoli, Pontian (International Journal of Criminology and Sociology, 2014)
The continual state of insecurity in Nigeria for several decades can be traced to a number of factors, including ethnic militias and religious fundamentalism. This article examines the extent to which such retrogressive phenomena are caused or fuelled by the proliferation of small arms in Nigeria. It examines the legal regime on small arms, non-legal but relevant societal issues and police powers as they concern the control of small arms proliferation in Nigeria. It argues that the extant legal regime is not robust enough to support any sustainable progress in this area. Also, it concludes that apart from a critical police overhaul and necessary municipal legislative action as influenced by international legal developments, practical policies and economic empowerment must be in place with a view to attaining sustainable development in the area of small arms control.